A new dawn for China's solar industry?. Issue 4 (October 2015) - Poon, Chun Yu Jonathan
Abstract : Chun Yu Jonathan Poon looks at the current status of China's solar industry, pondering where its future may lie after a series of scandals and international trade battles.